The Effect Of Corporate Board And Ownership Structure On Financial Performance - Abi R. Azira Nasution; Diantimala, Yossi; Yahya, M. Rizal (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
The study aims to investigate the effect of corporate board and ownership structure on company financial performance during the COVID-19 pandemic, focusing on industries highly affected in Indonesia and Singapore. Using quantitative methods, such as Multiple Linear Regression and considering firm size as a control variable, the study selected a sample through purposive sampling from the listed companies on IDX and SGX. It analysed secondary data from their annual reports between 2018 and 2020. The results show that the board size, board meetings, and managerial ownership positively and significantly affect the company's financial performance in the COVID-19 period. In Indonesia, board size and meetings positively affect a company's financial performance. In Singapore, institutional ownership and managerial ownership have a positive significance on corporate financial performance. Firm size significantly impacts company financial performance for countries in general and Indonesia, while Singapore has the opposite result.